Binaural Sound to Enhance Listening Comprehension in Language Tests - Magal-Royo, Teresa; Garcia-Laborda, Jesus (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The use of new digital formats in language learning and testing improves both the learning and acquisition skills development process of language tests. The process of listening comprehension is considered one of the most complex in the field of Computer Aided Learning Language (CALL) because it relates to multimodal learning channels and brain sound perception in an unfamiliar communication environment (the foreign language) for the learner. This article stresses the possibilities of using binaural sound in the design and implementation of tests as well as the cognitive issues that might be involved in the process of learning and assessment of a foreign language.